2016
DOI: 10.1021/acs.est.5b05809
|View full text |Cite
|
Sign up to set email alerts
|

Anionic, Cationic, and Nonionic Surfactants in Atmospheric Aerosols from the Baltic Coast at Askö, Sweden: Implications for Cloud Droplet Activation

Abstract: Recent analyses of atmospheric aerosols from different regions have demonstrated the ubiquitous presence of strong surfactants and evidenced surface tension values, σ, below 40 mN m(-1), suspected to enhance the cloud-forming potential of these aerosols. In this work, this approach was further improved and combined with absolute concentration measurements of aerosol surfactants by colorimetric titration. This analysis was applied to PM2.5 aerosols collected at the Baltic station of Askö, Sweden, from July to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(128 citation statements)
references
References 39 publications
8
120
0
Order By: Relevance
“…Aerosol chemical composition measurements challenge the assumption that the surface tension of activating particles is equal to that of water. Organic aerosols contain surface active molecules in sufficient abundance to reduce the surface tension of macroscopic solutions (4,7,8), and these abundances could, in principle, be sufficient to maintain a reduced surface tension throughout activation (7)(8)(9)(10)(11). Such a reduction could increase CCN concentrations by an order of magnitude (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol chemical composition measurements challenge the assumption that the surface tension of activating particles is equal to that of water. Organic aerosols contain surface active molecules in sufficient abundance to reduce the surface tension of macroscopic solutions (4,7,8), and these abundances could, in principle, be sufficient to maintain a reduced surface tension throughout activation (7)(8)(9)(10)(11). Such a reduction could increase CCN concentrations by an order of magnitude (12).…”
mentioning
confidence: 99%
“…Most approaches infer surface tension from hygroscopic growth or critical supersaturation measurements (28). Moreover, many studies report only macroscopic solution surface tension measurements and do not consider surfacebulk partitioning effects (4,7,8,16,29). Consequently, predictions of surfactant partitioning in aerosol are not accompanied by direct…”
mentioning
confidence: 99%
“…For instance, a notable amount of organic matter (up to 60 % of the total mass) was detected with a compact time-of-flight aerosol mass spectrometer in the CCN measured at the PUY station . Paying more attention to the effect of surfactants on cloud droplet formation follows the global interest that emerged in the literature (McNeill et al, 2013), with a multiplicity of laboratory and field studies as well as global modeling studies (Prisle et al, 2012) dedicated to this research area (Gérard et al, 2016;Nozière et al, 2014).…”
Section: Activation Of Aerosol Particles Into Cloud Dropletsmentioning
confidence: 99%
“…The parameterizations provided in these studies differ by the aerosol size distribution they use and the way they treat the activation process. They have been discussed by Simpson et al (2014) to demonstrate the effect of activating large particles described by a single lognormal mode simulation and by Ghan et al (2011), who concluded that all parameterizations performed well under the most common conditions, i.e., when CCN are mainly in the accumulation mode.…”
Section: Activation Of Aerosol Particles Into Cloud Dropletsmentioning
confidence: 99%